Materials characterization of innovative composite materials for solar-driven thermochemical heat storage (THS) suitable for building application. (18th December 2017) - Jarimi, Hasila; Devrim, Aydin; Zhang, Yanan; Ding, Yate; Ramadan, Omar; Chen, Xiangjie; Dodo, Auwal; Utlu, Zafer; Riffat, Saffa
Abstract: Thermochemical Heat Storage (THS) systems have recently attracted a lot of attention in research and development. One of the main parameters that influence the performance of a THS system is the thermochemical materials. This paper aims to investigate thermochemical materials which are suitable for both short-term and long-term building heat storage application driven by solar energy for an open system. Innovative composite materials using MgCl2 -MgSO4, CaCl2 -LiCl and MgSO4 - CaCl2 salts mixtures impregnated into vermiculite, and potassium formate (KCOOH) impregnated into silica gel will be presented in this study. Initial screening and characterization results of the composite THS materials based on the energy density using differential scanning calorimetry analysis, mass loss against temperature using thermo-gravimetric analysis, and moisture vapor adsorption isotherms testing are discussed. The characterization analysis suggest that the vermiculite with salts mixtures are promising candidates for thermochemical heat storage (THS) systems compared to composite materials with individual salts. Meanwhile the potential of KCOOH-silica gel as THS materials may be further investigated in the future. The performance of the materials may be further optimized in the future by changing the concentration ratio of the mixed salts.